The current economic state of the tourism industry of Pavlodar region and the assessment of strategic investments in its development - A. A. Titkov; S. Zh. Ibraimova; M. M. Begentayev; S. K. Kunyazova (Экономика: стратегия и практика)
The article examines the current state and economic trends in the functioning of the tourism industry of Pavlodar region. The object of the research is the economy of the Pavlodar region. In the course of the study, attention is focused on the dynamics of the nominal and real contribution of the tourism industry to the regional economy, the territorial distribution of tourism services and their structure in the context of types, trends in employment and labor productivity in the industry, production capacity and the state of their fixed capital. When assessing the real contribution of the tourism industry to the development of the regional economy, the dynamics of demand for tourism services from individuals and legal entities was investigated. For the development of the tourism industry in the region, an integrated analytical assessment of strategic investments has been made. Implementation of the developed investment policy makes it possible to significantly increase the volume of tourism services in the region, to strengthen the trends in the industry’s contribution to the economy. The results of the research can be used in the system of activities of regional, regional departments of tourism and sports in the Republic of Kazakhstan.